1989
DOI: 10.1007/bf01299687
|View full text |Cite
|
Sign up to set email alerts
|

Observation of nucleon clusters in the spontaneous decay of234U

Abstract: The emission of Ne and Mg nuclei was detected in the spontaneous decay of 234U with probabilities of, respectively, (3.9+1.0)• 10 -13 and (2.3_+0.7)• 10 -13 relative to a-decay. The upper limits of this kind of decay for 235U and 236U have been established. Systematics of half-lives for cluster emission are found to be similar to the Geiger-Nuttall dependence for a-decay. Some evidence for the presence of hindrance to cluster emission from the odd-mass nuclei 233U and 235U is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…the 24 Ne cluster is preformed faster in these parents as compared to other clusters. For the case of 234 U parent the cluster radioactivity is observed for 24,26 [62], but the cluster formation probability is maximum for 26 Ne cluster compared to other decays. We have computed the half life for these cluster emissions and it is found that the lowest half life time is for 26 [63] cluster decays are experimentally observed, i.e the 26 Ne cluster emission has the lower half life.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…the 24 Ne cluster is preformed faster in these parents as compared to other clusters. For the case of 234 U parent the cluster radioactivity is observed for 24,26 [62], but the cluster formation probability is maximum for 26 Ne cluster compared to other decays. We have computed the half life for these cluster emissions and it is found that the lowest half life time is for 26 [63] cluster decays are experimentally observed, i.e the 26 Ne cluster emission has the lower half life.…”
Section: Resultsmentioning
confidence: 89%
“…Coulomb and proximity potential model [32] and is found that the lowest half life time is for 14 and 26. In the case of 232 Th and 234,236 U parents the 24,26 Ne clusters are experimentally detected [59][60][61][62] but 26 Ne has the maximum preformation probability compared to 24 Ne cluster. Again the parents 230 Th, 231 Pa, 232,233,235 U have the maximum cluster formation probability for 24 Ne cluster as compared to 26 Ne cluster, i.e these clusters are formed very fast in these parents as compared to other clusters.…”
Section: Resultsmentioning
confidence: 91%
“…This discovery represented a milestone in the description of nuclear radioactivity as it bridged the gap between the α emission radioactivity and the standard fission reaction. Since then, cluster radioactivity (CR) has been found in twelve eveneven isotopes [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and seven odd-even isotopes (see, e.g., references in Refs. [22,23]) in the actinide region.…”
Section: Introductionmentioning
confidence: 99%
“…3, and Fig. 4 the experimental data for logarithmic half lives [4,[12][13][14][15][16][17][18][19] have been plotted against the mass numbers of parent nuclei along with the results of the present calculations for zero angular momentum of the fragments. In all the figures, the open circles depict the experimental data while the continuous line with solid circle represents the present calculations (MSAFM).…”
mentioning
confidence: 99%